The origins of international counterterrorism: Switzerland at the forefront of crisis negotiations, multilateral diplomacy, and intelligence cooperation (1969-1977) - Guttmann, Aviva (New perspectives on the Cold War, 2018)
Introduction -- Compliance, Coordination, and Censorship: Switzerland’s Response to Palestinian and Brazilian Terrorism -- -- Switzerland and Palestinian Terrorism: The 1969 Kloten Airport Attack and the 1970 Skyjack Sunday1 -- Switzerland and Brazilian Terrorism: The Abduction of Ambassador Bucher (1970–71) -- Conclusions of Part 1: A Comparison of Crisis Management -- At the Forefront through the Backdoor: Switzerland’s Counterterrorism Diplomacy -- -- Swiss Counterterrorism Diplomacy at the icao: “An Elegant Way of Doing Nothing” -- Swiss Counterterrorism Diplomacy at the un: A Fastidiously Balanced Position -- Swiss Counterterrorism Diplomacy at the CoE: Experts “Making” Foreign Policy -- Conclusions of Part 2: Swiss Counterterrorism Policymaking in Multilateral Fora -- In Defiance of Neutrality: Switzerland’s Secret Counterterrorism Cooperation -- -- A Secret Counterterrorism Alliance: Intelligence-Sharing within the Club de Berne (1971–1972) -- Conclusions of Part 3: A Glimpse into the Club de Berne in the 1980s -- Conclusions.